Beyond regimes China and India compared - Duara, Prasenjit; Perry, Elizabeth J. (Harvard contemporary China series, 2018)
"Contemporary China and India have been powerfully shaped by trans- and subnational forces. This volume approaches China and India via a strategy of "convergent comparison," exploring local and global influences through a focus on labor relations; legal reform and rights protest; public goods provision; and transnational migration and investment"--Provided by publisher.